2014
DOI: 10.1016/j.pnpbp.2013.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurochemical effects of repeated MDMA administration during late adolescence in the rat

Abstract: Adolescents and young adults disproportionately abuse 3,4-methylenedioxymethamphetamine (MDMA; ‘Ecstasy’); however, since most MDMA research has concentrated on adults, the effects of MDMA on the developing brain remain obscure. Therefore, we evaluated place conditioning to MDMA (or saline) during late adolescence and assessed anxiety-like behavior and monoamine levels during abstinence. Rats were conditioned to associate 5 or 10 mg/kg MDMA or saline with contextual cues over 4 twice-daily sessions. Five days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…With regard to the longstanding controversy on the role of 5-HT in the regulation of behavior in animal models of anxiety, Green and McGregor have suggested that MDMA-induced 5-HT depletion might produce either anxiolytic effects in rats with a high basal level of anxiety, or anxiogenic effects in rats with a low basal level of anxiety (Green and McGregor, 2002;Winstanley et al, 2004). However, a recent study by Cox and coworkers has refuted this speculation, by showing an anxiety-like behavior following repeated administration of MDMA and/or abstinence from MDMA (Cox et al, 2014).…”
Section: 2ratsmentioning
confidence: 99%
“…With regard to the longstanding controversy on the role of 5-HT in the regulation of behavior in animal models of anxiety, Green and McGregor have suggested that MDMA-induced 5-HT depletion might produce either anxiolytic effects in rats with a high basal level of anxiety, or anxiogenic effects in rats with a low basal level of anxiety (Green and McGregor, 2002;Winstanley et al, 2004). However, a recent study by Cox and coworkers has refuted this speculation, by showing an anxiety-like behavior following repeated administration of MDMA and/or abstinence from MDMA (Cox et al, 2014).…”
Section: 2ratsmentioning
confidence: 99%
“…The resulting supernatant was collected and diluted 1:4 in fluorescence dilution solution (0.01M HCl, 0.5mM EDTA, and 1mg/ml ascorbic acid). 39 HPLC columns are packed with very fine particles (stationary phase). The separation was done on Hypersil C18 (5 µm, 100 x 4.6 mm) columns, Surveyor, ThermoScientific Company, USA, with mobile phase as described later and the flow rate was 1.5 ml/min 25 o C.…”
Section: Estimation Of Serotonin (5-ht) Levels In the Cerebral Cortexmentioning
confidence: 99%
“…Concentrations of serotonin were quantified by interpolating peak areas relative to those generated by a range of standards that were run in parallel to unknowns and calculated as µg of 5-HT to mg of wet tissue weight. 39 …”
Section: Estimation Of Serotonin (5-ht) Levels In the Cerebral Cortexmentioning
confidence: 99%
“…A recent study examined the effects of repeated administration of MDMA (5 or 10 mg/kg, i.p., once daily for four days) to rats during late adolescence (PND 38–41) on place conditioning, anxiety behaviour, and monoamine levels (Cox et al, 2014). The treatment with 5 mg/kg of MDMA had no effect on any of the studied parameters.…”
Section: The Neurotoxicity Of Amphetamines To Adolescent Laboratory Amentioning
confidence: 99%